Ética crítica y política de las tecnologías. Ciudadanías mediadas en el Estado Plataforma. Análisis de Movilidad en Línea (2022)
The reflection on the role of a critical ethics that accompanies the technological innovation processes is presented, based on the contributions of the philosophy of technology, specifically the proposals of Floridi (2018) and Verbeek (2015). The case of digitization of government services will be analyzed, in the city of Medellin, Colombia, focused on the behavior of users of the Movilidad en Línea (Online Moblity) platform. The main thesis outlined is that digitalization processes are intended to eliminate the intermediation between the citizen and the access to the Platform State (Goupil, 2007; Massal and Sandoval, 2010). However, we find that intermediations persist and move towards technological intermediations. This finding and the demonstration of the agentiality and morality of technological artifacts support the proposal of a critical ethics that accompanies innovation and digital transition in a participatory way.